A Home Away from Home: Migration, Identity and 'Sojourning' in the Life of Uzbekistanis in Japan. Issue 10 (26th November 2022) - Dadabaev, Timur; Akhmedova, Mukaddam
Abstract: Using interview data, the article demonstrates that Uzbekistani residents of Japan understand and explain their stay in Japan largely as temporary, in line with the concept of 'sojourning'. In contrast to previous studies that operationalise sojourning according to legal status or 'preparations to return home', this article claims that such 'sojourning' needs to be treated as a constantly changing socially shaped discursive category employed by respondents to mitigate challenges such as economic hardship, discrimination and cultural assimilation. Additionally, male expatriates may describe their sojourning in culturally specific religious terms, as wanderers ( musofir ) in search of life experience abroad.